172 - MOTOR DEVELOPMENT OF GIRLS AND BOYS OF THE FOURTH YEAR OF PRIMARY EDUCATION (Fiep Bulletin - online, 2011)
This study aimed to diagnose motor delays of 80 children of both sexes, with 36 boys and 44 girls aged nine years, enrolled in the 4th year of primary education in public schools. All subjects were evaluated according to the two-dimensional model of Ozmum and Gallahue (2005), which classifies the fundamental motor skills in three stages: initial, elementary and mature. The skills tested were horizontal jump, lateral, rolling the body, balancing on one foot, throwing and kicking, so two movements in each category stabilizing, locomotor, manipulative, respectively. The data were presented in values of central tendency (mean), dispersion (standard deviation) and descriptive analysis, initially suffering a normality test of Shapiro-Wilking. The data showed a non-normal distribution and so we used the Mann-Whitney test for comparison between genders. All tests were performed in the computer software SPSS 14.0 for Windows, with the significance level of p
Keywords: Fundamental Motor Ability; Gender; Motor Evaluation